Question
Simplify the expression. \( -3 z-5 z \) \( -3 z-5 z=\square \)
Ask by Grant Bates. in the United States
Mar 09,2025
Upstudy AI Solution
Tutor-Verified Answer
Answer
\(-3z - 5z = -8z\)
Solution
\( -3z - 5z \) can be simplified by combining like terms.
1. Combine the coefficients:
\[
-3 - 5 = -8
\]
2. Multiply by \( z \):
\[
-8z
\]
Thus,
\[
-3z - 5z = -8z
\]
Answered by UpStudy AI and reviewed by a Professional Tutor
Like
error msg


Mind Expander
When you combine the like terms in the expression \(-3z - 5z\), you add the coefficients together. So, \(-3 - 5\) gives you \(-8\). Therefore, \(-3z - 5z = -8z\). So, the simplified expression is \(-8z\).